2013
DOI: 10.1212/wnl.0b013e31827b1a41
|View full text |Cite|
|
Sign up to set email alerts
|

Independent predictors of ischemic stroke in the elderly

Abstract: Characteristics related to neurologic impairment on admission were the main predictors of acute outcomes of IS in this cohort. Specific IS etiology and subtype influenced IS outcomes only after age 80. In oldest-old patients, demographics and prestroke functional and health status also influenced IS outcomes with peculiar associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…This scenario justifies the concern not only with the logistical support to the elderly, but also with the economic management and the actual effectiveness of intensive support in this population. The results of this study agree with the literature with regard to increased occurrence of stroke in elderly (13,19,20) , which reinforces the need for preventive measures to risk factors for stroke (20) , especially in primary attention and through active aging philosophy, with targeted actions not only to the elderly but also to the younger, seeking thereby prevent risks and reduce stroke hospitalization.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This scenario justifies the concern not only with the logistical support to the elderly, but also with the economic management and the actual effectiveness of intensive support in this population. The results of this study agree with the literature with regard to increased occurrence of stroke in elderly (13,19,20) , which reinforces the need for preventive measures to risk factors for stroke (20) , especially in primary attention and through active aging philosophy, with targeted actions not only to the elderly but also to the younger, seeking thereby prevent risks and reduce stroke hospitalization.…”
Section: Discussionsupporting
confidence: 90%
“…Among patients older than 65, stroke stands out as a major cause of hospitalization and prolonged hospitalization (19) . This scenario justifies the concern not only with the logistical support to the elderly, but also with the economic management and the actual effectiveness of intensive support in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In fact stroke's incidence increases with age in both genders, with an incidence of 38% in adults over 75 years old. [2][3][4] However, despite stroke's high prevalence in the elderly, intravenous alteplase (intravenous recombinant tissue plasminogen activator [IV-rtPA]), the only approved treatment for pharmacological revascularization in acute ischemic stroke, is licensed only in Europe for use in patients younger than 80 years old. 5 This seems to be related with frequent under-representation or exclusion of patients over the age of 80 years from clinical trials leading to uncertainty about the risk-benefit profile in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Guan et al showed patient with large artery infarction accompanied by low T3 level had severe neural damage leading to worse prognosis (14). Although several studies confirmed that serum T3 level is indeed an independent predictor of post stroke outcome still there are controversies regarding the association between thyroid hormone levels and post stroke recovery (15,16). An experimental data have shown that exogenous T3 administration helped in reducing the size of cerebral infarct and improve neurological deficit but there is still no conclusive answer whether treatment of low T3 level in acute stroke would improve the condition or not (17).…”
Section: Discussionmentioning
confidence: 99%